Analysis of Customers Transfer Opportunities Using Markov Chain at 3 Meatballs Culinary in Galuh Mas Karawang - Muhammad Harun; Agustian Suseno (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
The area of MSMEs meatballs culinary in Galuh Mas Karawang is a busy area and is often visited by the public. The purpose of this research is to determine the size of the consumer opportunities for the three meatballs culinary such as Ambon Meatballs, Malang Meatballs and Sopo Nyono Meatballs, and to predict the probability of their transfer in the coming period to the three meatballs culinary. The research sample consisted of 167 respondents who were only visitors and direct customers in March 2021. The research method was in the form of a questionnaire and analysis using the markov chain. The results showed that the steady state meatballs culinary in the 10th period of November 2021, it reached a balance point with the percentage for Ambon Meatballs is 54%, in the second place Sopo Nyono Meatballs is 25% and the lowest is Malang Meatballs 21%.